The androgen receptor couples promoter recruitment of RNA processing factors to regulation of alternative polyadenylation at the 3' end of transcripts. Issue 17 (31st August 2022) - Caggiano, Cinzia; Pieraccioli, Marco; Pitolli, Consuelo; Babini, Gabriele; Zheng, Dinghai; Tian, Bin; Bielli, Pamela; Sette, Claudio
Abstract: Prostate cancer (PC) relies on androgen receptor (AR) signaling. While hormonal therapy (HT) is efficacious, most patients evolve to an incurable castration-resistant stage (CRPC). To date, most proposed mechanisms of acquired resistance to HT have focused on AR transcriptional activity. Herein, we uncover a new role for the AR in alternative cleavage and polyadenylation (APA). Inhibition of the AR by Enzalutamide globally regulates APA in PC cells, with specific enrichment in genes related to transcription and DNA topology, suggesting their involvement in transcriptome reprogramming. AR inhibition selects promoter-distal polyadenylation sites (pAs) enriched in cis -elements recognized by the cleavage and polyadenylation specificity factor (CPSF) complex. Conversely, promoter-proximal intronic pAs relying on the cleavage stimulation factor (CSTF) complex are repressed. Mechanistically, Enzalutamide induces rearrangement of APA subcomplexes and impairs the interaction between CPSF and CSTF. AR inhibition also induces co-transcriptional CPSF recruitment to gene promoters, predisposing the selection of pAs depending on this complex. Importantly, the scaffold CPSF160 protein is up-regulated in CRPC cells and its depletion represses HT-induced APA patterns. These findings uncover an unexpected role for the AR in APA regulation and suggest that APA-mediated transcriptome reprogramming represents an adaptive response of PC cells to HT.